Coopération versus coordination : le travail collectif école-collège en tension - Chloé Lecomte (Recherches en Éducation)
The institutionalization of collective action between elementary school and middle school is a sign of the distinctiveness of the priority education policy in the fight against social and school-related inequalities. The requirement for teachers to set up "work collectives", which appeared in 2014, is part of a new method of regulation. Collective working arrangements are expected to foster peer self-regulation of the educational practices and organizations that are "the most effective" in student achievement. From a ethnographic survey in two priority education network, the paper deals with the situated effects of collective working required on the development of the cooperation and the interprofessional agreement-building between elementary school and middle school teachers.